Hispanic Use of Alternative Medicine as Demonstrated in Internet Searches - Yom-Tov, Elad; Strong, William F.; Strong, Lupita Rodriguez (Health Behavior Policy Review, 2017)
Objective: We investigated how cultural shifts occur with respect to the use of traditional medicine for influenza-like illness (ILI) within the Latino population near the US-Mexico border. Methods: We extracted searches of ILI treatments (modern, traditional western, and traditional Hispanic) to the Bing search engine from 5 US states near the US-Mexico border. The incidence of these searches was correlated with county-level demographic data and ILI incidence. Results: The fraction of queries related to Hispanic medicines is correlated with the distance from the US-Mexico border (Spearman rho = -0.24), which is a slower decay than that observed in the use of Spanish (Spearman rho = -0.35). Demographic and socioeconomic factors predict different searches for ILI treatments. Conclusions: People of Hispanic origin rely on traditional Hispanic medicines when treating ILI. Medical providers should guide their patients when such treatments might be clinically detrimental to patients, and know their patients are likely using such medicines.